1998
DOI: 10.1200/jco.1998.16.6.2253
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of recurrence following a negative sentinel lymph node biopsy in 243 patients with stage I or II melanoma.

Abstract: Regional nodal failures in melanoma patients following a negative SLN biopsy are infrequent and to date have most commonly occurred because conventional histologic evaluation was unable to identify occult metastatic disease. These data provide further evidence that lymphatic mapping and SLN biopsy accurately reflect the status of the regional nodal basin. Specialized pathologic techniques are necessary to reduce further the already low false-negative rates and to improve disease staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
236
3
14

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(273 citation statements)
references
References 14 publications
20
236
3
14
Order By: Relevance
“…This yields a false-negative sentinel rate of 9.2% and a failure rate of 2.2%, which is in accordance with previous studies (Gershenwald et al, 1999;Morton et al, 1999;Morton et al, 2003;Vuylsteke et al, 2003). As previously shown by Gershenwald, detection failure of positive SLNs most commonly occurs because conventional histologic evaluation is unable to identify occult metastatic disease (Gershenwald et al, 1998). Furthermore, Morton reported a statistical lack in the detection of a positive SLN in patients with primary melanoma o2.01 mm: Compared to the incidence of regional lymph node metastasis in a historical control group of patients who where treated by wide local excision only (WLE), incidence of a positive SLN is only 60%.…”
Section: Discussionsupporting
confidence: 90%
“…This yields a false-negative sentinel rate of 9.2% and a failure rate of 2.2%, which is in accordance with previous studies (Gershenwald et al, 1999;Morton et al, 1999;Morton et al, 2003;Vuylsteke et al, 2003). As previously shown by Gershenwald, detection failure of positive SLNs most commonly occurs because conventional histologic evaluation is unable to identify occult metastatic disease (Gershenwald et al, 1998). Furthermore, Morton reported a statistical lack in the detection of a positive SLN in patients with primary melanoma o2.01 mm: Compared to the incidence of regional lymph node metastasis in a historical control group of patients who where treated by wide local excision only (WLE), incidence of a positive SLN is only 60%.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, previous studies involving melanomas from all anatomic sites showed a statistically significant improvement in survival in patient with intermediate thickness melanomas (range, 1-4 mm), which suggests that some subgroups of patients may benefit from ELND 3,25,31 . Finally, despite the fact that sentinel lymph node biopsy (SLNB) has been adopted into clinical practice as reliable staging modality, there are lots of arguments against it, such as increased incidence of nodal (regional and in-transit) recurrence in sentinel lymph nodes (SLN) negative patients, possibility of false-negative results, difficult identification of SLN if they are located close to primary site, SLN found in multiple node fields in contrast to melanomas located on extremities which usually drain to only 1 field, SLN in parotid region which are often very small, may be difficult to find, and their removal may put the facial nerve at risk 8,10,12,15,16,29,36,37 . However, some authors reported that intraparotid SLN biopsy is a reliable, accurate, and safe procedure for staging cutaneous head and neck melanoma 23 .…”
Section: Discussionmentioning
confidence: 99%
“…With long-term follow-up of patients with negative sentinel nodes there is a small but definite incidence of recurrence in the mapped and sampled nodal basin. 5,[10][11][12][13][14][15][16][17][18][19] These patients may be considered to have a false-negative result of their sentinel node biopsy procedure. Previous reports have suggested that the majority of patients who recur in the relevant node field will, in fact, have identifiable metastases in the biopsied sentinel node if a more comprehensive histopathologic evaluation of the node is undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that the majority of patients who recur in the relevant node field will, in fact, have identifiable metastases in the biopsied sentinel node if a more comprehensive histopathologic evaluation of the node is undertaken. 10,14 However, a review of the results of sentinel node biopsy procedures at the Sydney Melanoma Unit has suggested that an incorrect histopathologic diagnosis has been responsible for only a minority of regional failures in Sydney Melanoma Unit patients. 15 One possible reason for this is that all sentinel node specimens have been assessed with multiple sections and immunohistochemical stains since the introduction of the technique at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation